Hydrolytic enzymes from pseudomonas aeruginosa - Gagalac, Marilou G.
The extracellular cornea-damaging substances of Pseudomonas aeruginosa were studies and characterized with regards to the enzymatic activities associated with them. The ammonium sulfate (AS) precipitate was fractionated in Sephadex G-75, resolving two active components and in DEAE-Cellulose chromatography, resolving four opacification factors. Enzymatic and cornea-damaging activity assays and lyophilization experiments showed that opacification could be due to proteolytic and hyaluronidase activities on corneal proteoglycans. Studies on the effects of growth conditions and simulation of in vivo conditions by addition of corneal materials to the culture medium showed that the enzymes studied are inducible.